Short story: disease takes happiness away / Nur Amira Natasha Zaidie Amir and Muhammad Rozman Abdullah - Zaidie Amir, Nur Amira Natasha; Abdullah, Muhammad Rozman (Academy of Language Studies, 2023)
This century has witnessed technology as an element that contribute to the thriving of people's activity, social media, games, music. Despite that, one activity that people tend to dislike is reading. Even though there is an e-book option, it is still not exciting and robust enough to make people read. Reading can take a huge total, especially an English novel. This is probably because the word or sentence is hard to understand. English may be a second language in Malaysia but there are still plenty of people who are struggling with it. So, the creation of short story to help people develop their English skills Thus, this paper explains how a short story can help to spark the interest of people of all ages to read. To capture readers' attention, a story about a cat owner's experience with a cat with a disease was produced. The purpose of this paper is to encourage people to read English short stories. Technical vocabulary is the language theory used in this project. According to (Nation, 2001), technical vocabulary is one of the high-frequency terms that account for around 80% of the running words in academic publications and newspapers, as well as approximately 90% of conversation and novels. A survey was conducted among cat owners which consist of three sections; demographic, pet owners' background and cat diseases. Pet owners recommend providing daily check-ups to the clinic to avoid worse conditions towards cats.